A Case Report of Autosomal Dominant Polycystic Kidney Disease Under Peritoneal Dialysis With Cyst Infection and Culture-Positive Peritoneal Fluid. Issue 12 (April 2019) - Yasuda, Itaru; Hasegawa, Kazuhiro; Tokuyama, Hirobumi; Washida, Naoki; Shinozuka, Keisuke; Yasuda, Marie; Ryuzaki, Masaki; Urai, Hidenori; Wakino, Shu; Itoh, Hiroshi
Background: Cyst infection is a complication sometimes seen in patients with autosomal dominant polycystic kidney disease (ADPKD) and often shows through a positive blood culture. However, there have been no reports of ADPKD patients whose cyst infection propagate to peritoneal fluid leading to positive peritoneal fluid culture. Case presentation: A 74-year-old Japanese man with ADPKD under peritoneal dialysis (PD) was presented with left flank pain, fever, and chills at our hospital. He did not show any symptoms or signs suggestive of peritonitis. There were no elevated cell counts or polymorphonuclear leucocytes in his PD fluid. There were some complicated cysts found in computed tomography and magnetic resonance imaging examinations. We clinically diagnosed him as having a renal cyst infection rather than PD-related peritonitis. We initiated treatment by administering ceftriaxone with an immediate favorable response. As the possibility of accompanying prostatitis still remained, we switched to intravenous levofloxacin on the second day. On the 10th day, Helicobacter cinaedi was detected in 2 sets of blood culture as well as in PD fluid. We switched back to ceftriaxone and this treatment was entirely successful. Conclusions: This is the first report of H cinaedi cyst infection which propagates to peritoneal fluid in a patient with ADPKD.